Changing satire : Transformations and continuities in Europe, 1600-1830 - Wingård, Rikard; Sivefors Per; Rosengren Cecilia (Book collections on Project MUSE., 2022)
This edited collection, with contributions from literary scholars and art historians, maps how satire became a less genre-driven and increasingly visual medium in the early modern period. It features material on several European countries and demonstrates the range and diversity of satire in the period 1600 to 1830.